Co-occurring Cuban dwarf boas (Tropidophis) show limited dietary differentiation - Tomás M. Rodríguez-Cabrera; Javier Torres; Ernesto Morell Savall (Herpetozoa)
Interspecific and intraspecific niche partitioning have been widely documented in sympatric snakes. Size variation and ecological differentiation in co-occurring Tropidophis in Cuba suggest differences in diet. We compared dietary composition and niche breadth among three species of Tropidophis in central Cuba: T. pardalis (n = 13), T. semicinctus (n = 28), and T. melanurus (n = 86; 80 large, 6 small individuals). We found complete overlap in diet composition among T. pardalis, T. semicinctus, and small T. melanurus, all of which specialized on lizards of the genus Anolis. In contrast, large T. melanurus had a distinct diet, consisting mostly of amphibians (95%), particularly the Cuban treefrog (Osteopilus septentrionalis; ca. 70%) and two species of toads of the genus Peltophryne (ca. 26%), suggesting an ontogenetic shift in the diet of T. melanurus. The three species of Tropidophis had a narrow trophic niche (B′ ≤ 0.280).